ЗАВИСИМОСТЬ СОПРОТИВЛЕНИЕ РАСТЕКАНИЯ ОТ ДИАМЕТР МИКРОПЛАЗМЫ, ДИФФЕРЕНЦИАЛЬНАЯ СОПРОТИВЛЕНОЕ РАСТЕКАНИЯ МИКРОПЛАЗМ И ЕГО РАСПРЕДЕЛЕНИЯ РЯДУ ТЕЙЛОРА И РЕШЕНИЯ СИСТЕМ ФУНКЦИИ МЕТОДОМ КОШИ - Абдреймов, А.А.; Мадияров, Д.Н.; Хожамуратова, А.Р. (SCIENCE and SOCIETY, 2023)
Taking into account the three-dimensional distribution of the electric field of moving charge carriers, we accurately formed the spreading resistance. A comparison of theoretical and experimental values showed that the proposed model is in good agreement with the exact parameters of the microplasma, the studies were carried out on the basis of the microplasma characterization method. The calculation of the range of spreading resistances proposed in this work makes it possible to refine the equations for the microplasma diameter.